J.-P. SARTRE’S HUMANISM IN THE CONTEXT OF MODERN ANTHROPOLOGICAL SITUATION - V. V. Liakh; M. I. Khylko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is aimed to show the specificity and heuristic value of the humanism of the French existentialist J.-P. Sartre, represented both in his early works, where the isolationist position prevailed, and considering his evolution to various types of collective responsibility and attempts to build a universal morality on the basis of ontological integral humanity. Theoretical basis. Taking into account the relevance of the topic of person’s searching for authentic existence in the modern world, the author analyzes the concept of Sartre’s humanism, which remains poorly researched in the Ukrainian philosophical space, since most of his works of the later period remained untranslated and unknown to the Ukrainian community. That is, there is a need to consider the phenomenon of a human and his/her basic characteristics, which ultimately determine what type of humanism deserves further support and development. The author places the existentialist dimension of a human being, which is one of the most important determinants of human behavior and the ways of human self-determination of his/her existence, in the context of the general development of the humanistic tradition of modern anthropology. Originality. The article substantiates the thesis that Sartre’s position concerning humanism is conditioned by the specificity of his understanding of the authentic human existence as a constant self-transcendence, the person’s realization of the project that makes a person the creator of the values. Therefore, Sartre’s humanism can only be understood in the context of this self-construction and responsibility of a person for his/her choice. The author proved that although this concept was subsequently changed, the basic intention of the Sartre’s approach remains the same. Thus, having combined the existentialism and Marxist understanding of the historical process, Sartre nevertheless emphasizes that the primal intentionality of human existence (project or transcendence) is decisive in all subsequent actions and doings, despite the fact that real practice may demonstrate deviations and even regression concerning humanity. Having defined the universality of the human situation in the world as the presence of certain a priori restrictions, the philosopher comes to the recognition of intersubjectivity, which allows him to reach a new type of morality, which defines "integral humanity" or "full-fledged human" as its goal. Conclusions. The interpretation of humanism by early Sartre relied on the idea of a person as such, who is in constant transcendence (going beyond), constantly constructing him/herself; he/she is oriented towards the future (but it is a pure future, unplanned and undefined). In this case, a person is the creator of the values and their legislator in this world. At the same time, the late Sartre emphasized that since a person exists in a society where he/she is usually in a state of alienation, the question under which conditions and by what means is it possible to reproduce and realize a truly humanistic dimension is inevitable. Sartre’s position is based on the fact that there is a primal need for self-realization, to be human.